2022
DOI: 10.1101/2022.04.29.490072
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Histone deacetylase 6 inhibition promotes microtubule acetylation and facilitates autophagosome-lysosome fusion in dystrophin-deficient mdx mice

Abstract: Duchenne Muscular Dystrophy (DMD) is a severe X-linked genetic disorder. Defective autophagy and disorganized microtubule network contributes to DMD pathogenesis, yet the mechanisms by which microtubule alterations regulate autophagy remain elusive. We show decreased acetylated α-tubulin and enhanced histone deacetylase (HDAC6) expression in mdx mice. Pharmacological inhibition of HDAC6 increases tubulin acetylation and enhances Q-SNARE complex formation, leading to improved autophagosome-lysosome fusion. HDAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…A recent study showed in mdx mouse myoblasts that increased phosphatidylinositol-3,4,5-trisphosphate 3-phosphatase (PTEN) signaling led to upregulated autophagosome formation but yielded a reduced overall flux [100], suggesting defective autophagy. It is worth noting that our group has since identified increased Nox2-derived ROS and decreased acetylation of α-tubulin as unrelated disruptors of autophagosome-lysosome fusion in mdx mice (under review [101]), suggesting that multiple perturbed pathways may converge to cause impaired autophagy. Together, these findings suggest that increased oxidative stress in mdx mice perturbs pathways involved in blood clotting and immune response, but also potentially has a strong effect on autophagic mechanisms that are critical for muscle regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed in mdx mouse myoblasts that increased phosphatidylinositol-3,4,5-trisphosphate 3-phosphatase (PTEN) signaling led to upregulated autophagosome formation but yielded a reduced overall flux [100], suggesting defective autophagy. It is worth noting that our group has since identified increased Nox2-derived ROS and decreased acetylation of α-tubulin as unrelated disruptors of autophagosome-lysosome fusion in mdx mice (under review [101]), suggesting that multiple perturbed pathways may converge to cause impaired autophagy. Together, these findings suggest that increased oxidative stress in mdx mice perturbs pathways involved in blood clotting and immune response, but also potentially has a strong effect on autophagic mechanisms that are critical for muscle regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding class IIb HDACs, two independent groups identified interesting functions for HDAC6 in DMD [137,138]. HDAC6 exclusively localized in the cytoplasm, where it removes acetyl groups from non-histone proteins such as α-tubulin, modulating microtubule network stability and organization [49].…”
Section: Histone Deacetylases In Muscular Dystrophiesmentioning
confidence: 99%
“…Increased HDAC6 protein expression has been reported in mdx muscles, with a concomitant reduction of acetylated α-tubulin, which contributes to the disorganization of microtubule network and to the impairment of the autophagic flux in DMD. The pharmacological inhibition of HDAC6, by tubastatin A administration, restores the microtubule acetylation and rescues the autophagic flux enhancing autophagosome-lysosome fusion in mdx mice, in addition to improve AChR clustering and distribution [137,138]. Moreover, HDAC6 inhibition downregulates transforming growth factor beta (TGF-β) signaling, through an increase of SMAD2/3 acetylation, thereby reducing muscle atrophy and fibrosis and improving protein synthesis in mdx muscles [137].…”
Section: Histone Deacetylases In Muscular Dystrophiesmentioning
confidence: 99%